Assessing the Impact of Three-Wheelers on Traffic Flow in India: A Case Study Using Ann - Mohanty, Malaya; Pattanaik, Madhu Lisha; Ranjan Samal, Satya; Shivam (Communications - Scientific Letters of the University of Zilina, 2024)
This study explores the significant role of three-wheelers (3W) on urban road traffic, focusing on the reduction in average vehicle speeds and its consequential impact on the Level of Service (LOS) of the road. Data collected from various traffic volumes reveal significant speed reductions ranging from 4 % to 35 % due to the movement of 3Ws on the road. To model this phenomenon, Artificial Neural Network (ANN) is employed. The resulting reductions in speed, induced by the 3W, trigger LOS degradation, leading to congestion and delays. A noteworthy finding is that the traffic flow naturally gravitates towards the LOS C, underscoring the substantial role played by the 3W in diminishing the overall LOS of the road. This research offers critical insights into the dynamics of urban traffic influenced by the 3W, providing a valuable foundation for traffic management and urban planning efforts.
Keywords: three-wheelers (3W) traffic flow average speed reduction congestion level of service (LOS) artificial neural network (ANN) speed modelling